Contribution of Turkish stock market to global portfolios - Onay, Ceylan. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2004., 2004)
In this research, the long term international diversification benefit of Turkish Stock market is investigated among globally and regionally constructed portfolios. The global portfolios are Developed Markets, Emerging Markets and World portfolios. The regional portfolios are Developed Europe, Emerging Europe, Asia, North America, Latin America, Pacific Rim, Middle East and G7 portfolios. In the research, mean-variance portfolio theory is employed using the dollar denominated monthly MSCI country stock index data and diversification benefit is explored in the full period as well as in the crises periods. Furthermore, due to the limitations of the mean-variance framework, Stein estimation is used to verify the findings of the study free of estimation bias. Under each optimization, the statistical significance of the findings are explored with the asset set spanning and asset set intersection tests of the Jobson and Korkie, respectively for the efficient portfolios constructed in the absence and in the presence of a riskless asset. This study specifically focused on the diversification potential of Turkish stock market. In this respect, the findings of the study reveal whether or not investment in it had been beneficial for an international investor for risk reduction purposes. It is found that despite its relatively lower correlations, over the investigation period Turkish stock market's contribution to reduce the risk of a global portfolio is negligible.``PA@`P`P`@@`@Pp@0` Pp@P`P0@P`Pp`@@`P @0` Ppp@``pP@P@`P`Pp@@@`pP@0`Ppp@P`PP0@P`Pp@@`P @@0`0Pp@``PA@`P`P`@@`@Pp@0` Pp@P`P0p@P`PpP@@`P @0` Pp@``pP@@`P`Pp@@`pPp@0`Pp@P`PP0@P`Ppp@@`P @0`0Pp@``PA@@`P`P`@@`@Pp@0` Pp@P`PA@P`Pp`@@`P @0` Ppp@``pPRp@`P`Pp@@@`pP@0`Ppp@P`PP0@P`Pp@@`P P@0`0Pp@``PA@`P`P`@@`@Pp@0` Pp@P`P0@P`PpP@@`P @0` Pp@``pP@@`P`Pp@@`pPp@0`Pp@P`PPA@P`Ppp@@`P @0`0Pp@``PA @`P`P`@@`@Pp@0` Pp@P`P0@P`Pp`@@`P @0` Ppp@``pP@@`P`Pp@@@`pP@0`Ppp@P`PP0@P`Pp@@`P @@0`0Pp@``PA@`P`P`@@`@Pp@0` Pp@P`P0p@P`PpP@@`P @0` Pp@``pP@@`P`Pp@@`pPp@0`Pp@P`PP0@P`Ppp@@`P @0`0Pp@``PA`@`P`P`
Keywords: Stock exchanges -- Turkey.